Kesesuaian Lahan Tanaman Kelapa Sawit di Kecamatan Ranah Batahan Menggunakan Fuzzy Logic - Wilda Safitri; Febriandi Febriandi (Lembaga Yasin AlSys, 2026)
Oil palm is one of Indonesia’s key plantation commodities, producing edible oil, industrial oil, and biofuel (biodiesel) and contributing positively to economic and social development. This study aimed to: (1) analyze land suitability for oil palm in Ranah Batahan Subdistrict using fuzzy logic; and (2) determine oil palm productivity levels in Ranah Batahan Subdistrict. Land suitability analysis was conducted using a fuzzy logic approach to the area’s biophysical conditions, while oil palm productivity data were obtained from the Central Bureau of Statistics (BPS) of Ranah Batahan Subdistrict. The results show that, based on land suitability analysis using fuzzy logic, land for oil palm cultivation in Ranah Batahan Subdistrict is classified into two categories: moderately suitable and highly suitable. The area categorized as moderately suitable covers 12,420.53 hectares (43.17%), whereas the highly suitable area extends over 17,174.79 hectares (56.83%) of the total area of Ranah Batahan Subdistrict. Oil palm production data indicate that Nagari Batahan Selatan is the nagari with the highest oil palm production, reaching 50 tons, while the lowest production is found in Nagari Desa Baru, at 10 tons. These findings confirm that most of Ranah Batahan Subdistrict has a high level of land suitability for oil palm development, while also revealing inter-nagari variation in productivity that is important to consider in planning and managing local oil palm development.